Finite element analysis of steel arch frame using ANSYS - Ahmad Wafiq Firdaus, Zulkifli (2015)
In this study, A arches are a continuous-curve, plane, structural elements usually lie in a vertical plane designed to carry load, especially vertically. The main characteristic is the ability to move the arch of the external load through the power mainly, with the support of the compression. The 3D arch frame analysed by manual calculation and ANSYS program with the probability method. This analysis is to determine the stress, strain, deflection and deformation. In addition, the structure is examined according to Eurocode 3 as well. It is very stable in terms of everything and low cost. Materials and space truss geometry satisfied for this study because it passed all design criteria in the design of tension, compression and buckling. Numerical results show very good agreement with the results of manual calculations. From the simulation results, we recognize the actual behaviour of the structure under the applied load. In the analysis of probability, we get the results of the cumulative distribution function, histogram plot, and history plot sensitivity easily by 10,000 times simulation for any input and output